Defining Vasoplegia Following Durable, Continuous Flow Left Ventricular Assist Device Implantation. Issue 1 (10th May 2021) - Swan, Joshua T.; Iso, Tomona; Rizk, Elsie; Trachtenberg, Barry H.; Krisl, Jill; Varnado, Sara; Suki, Wadi N.; Frost, Adaani E.; Suarez, Erik; Uddin, Faisal S.; Kassi, Mahwash; Giesecke, Noel Martin; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : This study aimed to develop a definition of vasoplegia that reliably predicts clinical outcomes. Vasoplegia was evaluated using data from the electronic health record for each 15-minute interval for 72 hours following cardiopulmonary bypass. Standardized definitions considered clinical features (systemic vascular resistance [SVR], mean arterial pressure [MAP], cardiac index [CI], norepinephrine equivalents [NEE]), threshold strategy (criteria occurring in any versus all measurements in an interval), and duration (criteria occurring over multiple consecutive versus separated intervals). Minor vasoplegia was MAP < 60 mm Hg or SVR < 800 dynes⋅sec⋅cm −5 with CI > 2.2 L/min/m 2 and NEE ≥ 0.1 µg/kg/min. Major vasoplegia was MAP < 60 mm Hg or SVR < 700 dynes⋅sec⋅cm −5 with CI > 2.5 L/min/m 2 and NEE ≥ 0.2 µg/kg/min. The primary outcome was incidence of vasoplegia for eight definitions developed utilizing combinations of these criteria. Secondary outcomes were associations between vasoplegia definitions and three clinical outcomes: time to extubation, time to intensive care unit discharge, and nonfavorable discharge. Minor vasoplegia detected anytime within a 15-minute period (MINOR_ANY_15) predicted the highest incidence of vasoplegia (61%) and was associated with two of three clinical outcomes: 1 day delay to first extubation (95% CI: 0.2 to 2) and 7 day delay to first intensive care unit discharge (95% CI: 1 to 13). The MINOR_ANY_15 definition should be externally validated as an optimal definition of vasoplegia.